Desa Cibinong sebagai desa percontohan budi daya ikan hias dimasa pandemi Covid-19 - Fathimah, Nur Sabrina; Maulidah, Inas Nabilatul; ., Jumeri; Hamidah, Anis; Safitri, Wiena (Universitas Sam Ratulangi, 2022)
The aim of this study is to explore the methods, strategies, and other aspects of cultivation activites in Cibinong Village that potentially lead this village to become pilot village for ornamental fish cultivation during the COVID-19 pandemic. This study use qualitative method through interviews, observations, and documentation. The availability of land to make ponds in almost every resident’s house, abundant water supply, strategic position that close to the center of ornamental fish market, and willingness to share experience between resident are important aspects that make this village become successful in cultivation of ornamental fish. After analyzing and exploring it can be concluded that Cibinong Village in Gunung Sindur District can become one of the pilot villages for ornamental fish cultivation during the COVID-19 pandemic.